Mental Health in the Medical Home: A Longitudinal Curriculum for Pediatric Residents on Behavioral and Mental Health Care - Nicole Meyers; Beth Maletz; Evelyn Berger-Jenkins; Mariellen Lane; Erin Shindle; Marguerite Costich; Steve Caddle; Connie Kostacos; Gabriella Paskin; Kalpana Pethe; Sydney Shope; Marina Catallozzi; et al. (Association of American Medical Colleges, 2022)
Introduction Currently, a pediatric mental and behavioral health crisis exists, driven by increasing stressors among children coupled with a paucity of psychiatric providers who treat children. Pediatric primary care providers can play a critical role in filling this gap, yet trainees feel uncomfortable screening for, identifying, and managing mental and behavioral health conditions among their patients. Thus, expanding training for pediatricians in this domain is critical. Methods We created a longitudinal integrated mental and behavioral health curriculum for pediatric residents at NewYork-Presbyterian/Columbia University Irving Medical Center with a logic model contextualizing outpatient pediatric care as a framework for the development and planned evaluation. We devised a comprehensive set of materials, with presentations on topics including attention deficit hyperactivity disorder and anxiety disorders. Workflows and escalation pathways promoting collaboration among interdisciplinary providers were implemented. We evaluated residents' and faculty members' participation in the curriculum and their perception of curricular gaps. Results Approximately 155 pediatric residents participated in the curriculum from 2017 to 2021, reflecting robust curricular exposure. Few residents and no preceptors perceived mental and behavioral health as a curricular gap. Discussion Our curriculum is feasible and can be adapted to a variety of educational settings. Its use of a logic model for development, implementation, and ongoing evaluation grounds the curriculum in educational theory and can address curricular gaps. The framework can be adapted to suit the needs of other institutions' educational and practice settings and equip pediatric trainees with the skills to promote patient mental health and well-being.